The mediating role of marital boredom in the relationship between emotional divorce with self-differentiation and communication patterns of couples - Mahrokh Sadat Rasti; Mansoureh Amirshahi; Shakila Ghaznavi (Shahid Beheshti University of Medical Sciences, 2024)
Background: Emotional divorce by creating an emotional rift in the family can be the main cause of family frustration. This study aimed to investigate the relationship between emotional divorce and self-differentiation and the mediating role of marital boredom in couples referring to counseling centers. Methods: This practical research was carried out on couples referred to counseling centers in Tehran, in 2021. In this study, one hundred people were selected by convenience sampling. The data were gathered by the Emotional Divorce, Self-Differentiation (DSI-SF), Communication Patterns (CPQ) and Marital Boredom Questionnaires. Data analysis was done using the Pearson correlation test and structural equation modeling (SEM). Results: The results of the Pearson correlation test indicated positive and significant relationships between all research variables. According to the results of SEM, the variables of differentiation and communication patterns of couples had a direct effect on emotional divorce. Moreover, differentiation and communication patterns showed an indirect effect on marital divorce through marital boredom. Conclusion: The findings showed that the factors of differentiation, behavioral patterns and boredom could cause emotional divorce between couples. It is recommended to pay much attention to the differentiation of people during marriage so that they can prevent marital boredom and emotional divorce by creating appropriate communication patterns with their spouses.